Sexual functioning after total versus subtotal laparoscopic hysterectomy - Berlit, Sebastian; Tuschy, Benjamin; Wuhrer, Anne; Kircher, Anna-Theresa; Sütterlin, Marc; Lis, Stefanie; Hornemann, Amadeus (Archives of gynecology and obstetrics, 2018)
AimTo evaluate postoperative sexual functioning and the influence of patients’ expectations on the change in sexuality following laparoscopic total (TLH) versus subtotal hysterectomy (LASH).MethodsA total of 120 women undergoing laparoscopic hysterectomy were preoperatively enrolled in this bicentric prospective study. Sexual functioning (SF) was evaluated using the female sexual function index (FSFI). Additionally, participants filled in a standardised questionnaire concerning expected changes in SF after surgery. At 3, 6 and 12 months following surgery, women were asked again to assess their level of SF (FSFI). Data of women who participated in at least one FSFI follow-up assessment were analysed (n = 92). We compared the change in SF after surgery between patients with TLH (n = 46) and LASH (n = 46). Additionally, we calculated regression analyses with the patients’ expectations as a predictor for change in FSFI scores.ResultsComparing the change of FSFI scores after surgery in both collectives revealed differences only 3 months after surgery, as improvement was stronger for the LASH collective compared to the THL group (p = 0.006). There were no changes comparing collectives after 6 (p = 0.663) and 12 (p = 0.326) months. Concerning patientsʼ expectations, for the LASH group baseline SF (p < 0.001), but not expectations (p = 0.567) predicted the strength of change at each of the follow ups: a lower level of baseline SF was linked to a stronger improvement after surgery. For the THL collective, both baseline SF (p < 0.001) as well as patients’ expectations (3 months: p = 0.077, 6 months: p = 0.37, 12 months: p = 0.024) predicted the strength of change: both, a lower level of baseline SF and higher expectations towards an improvement predicted a stronger improvement.ConclusionThe preservation of the cervix does not show an advantage in improving SF after surgery. Both methods induce a comparable improvement in long-time SF, especially in patients with an impaired sexuality pre-surgery. Furthermore, patients’ expectations concerning this matter seem to have an impact on the postoperative outcome; therefore, this circumstance should be considered in future projects.